2016
DOI: 10.1016/j.chom.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV and IFN: Too Little, Too Late

Abstract: Dysregulated type I interferon (IFN-I) expression can lead to severe pathology and disease. In this issue of Cell Host & Microbe, Channappanavar et al. (2016) use a SARS-coronavirus animal model to describe how rapid and robust virus replication with delayed IFN-I can lead to lung immunopathology, with fatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 11 publications
(7 reference statements)
1
98
0
4
Order By: Relevance
“…Viral RNAs are recognized by the innate immune system through three major classes of cytoplasmic pattern recognition receptors: Toll-like receptors (TLRs), RIG-I-like receptors (RLRs) and NOD-like receptors (NLRs), which trigger the expression of interferon (IFN) and activation of anti-viral effectors such as Natural Killer cells, T CD8 + cells and macrophages [7][8][9][10]. Coronaviruses, such as SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV), have evolved strategies to dampen or delay IFN production, which usually trigger exuberant inflammatory host responses leading to severe lung pathology [8,[11][12][13]. It is believed that dysregulated host immune response and production of inflammatory cytokines, known as the "cytokine storm", correlates with disease severity and poor prognosis during SARS-CoV and MERS-CoV infection [8,9,14].…”
Section: Introductionmentioning
confidence: 99%
“…Viral RNAs are recognized by the innate immune system through three major classes of cytoplasmic pattern recognition receptors: Toll-like receptors (TLRs), RIG-I-like receptors (RLRs) and NOD-like receptors (NLRs), which trigger the expression of interferon (IFN) and activation of anti-viral effectors such as Natural Killer cells, T CD8 + cells and macrophages [7][8][9][10]. Coronaviruses, such as SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV), have evolved strategies to dampen or delay IFN production, which usually trigger exuberant inflammatory host responses leading to severe lung pathology [8,[11][12][13]. It is believed that dysregulated host immune response and production of inflammatory cytokines, known as the "cytokine storm", correlates with disease severity and poor prognosis during SARS-CoV and MERS-CoV infection [8,9,14].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV applies several mechanisms to overcome the immune response. First, it inhibits the rapid expression of interferon type 1 (IFN-1) (2). IFN-1 is known as the "initial alarm" upon encounter with the virus that modulates the immune cells to the so-called "antiviral state".…”
Section: Introductionmentioning
confidence: 99%
“…This two-pronged strategy of nsp1 inhibits expression of the IFN gene (Kamitani et al, 2006;Narayanan et al, 2008;Wathelet et al, 2007). Murine models of SARS-CoV have revealed that the dysregulated type I IFN response is a key factor for inducing lethal pneumonia (Channappanavar et al, 2016;Kindler and Thiel, 2016). In addition, Züst and colleagues showed that a mutant MHV with partial deletion in nsp1 is highly attenuated (Züst et al, 2007).…”
Section: Introductionmentioning
confidence: 99%